Estimation of Contaminants for Direct Imaging of Exoplanets: Constraint on the Stellar Distribution Model with both NIR and Deep Imaging Data. Issue Volume 8:Issue S299(2013) (6th January 2014) - Konishi, Mihoko; Shibai, Hiroshi; Matsuo, Taro; Yamamoto, Kodai; Sudo, Jun; Samland, Matthias S.; Fukagawa, Misato; Sumi, Takahiro; ,
Abstract: There are faint contaminants near primary stars in the direct imaging of exoplanets. Our goal is to estimate statistically the ratio of exoplanets in the detected batch of point sources by calculating the fraction of contamination. In this study, we compared the detected number of stars with the number of contaminants predicted by our model. We found that the observed number of faint stars were fewer than the predicted results towards the Pleiades and GOODS-South field when the parameters of the conventional stellar distribution models were employed. We thus estimated new model parameters in correspondence to the results of the observations.